Phase behavior and ternary diagram construction for membrane forming polycarbonate solutions - Idris, A. (Trans Tech Publications Ltd, 2014)
Cloud points at different polymer concentrations were obtained by the simple titration method and compared with the numerically calculated theoretical binodal curves for Polycarbonate/Dimethylacetamide/Water (PC/DMAc/Water) and Polycarbonate/N-Methyl-2- pyrrolidone/Water (PC/NMP/Water). The interaction parameters for solvent polymer and nonsolvent polymer were obtained from Hansen's solubility parameters. The cloud points determined were found to be in close agreement with the theoretical binodal curve calculated. Coagulation values for different solvents such as Dichloromethane (DCM), Dimethylacetamide (DMAc), N-Methyl-2-pyrrolidone (NMP) and Tetrahydrofuran (THF) were also determined and the results were plotted in a ternary diagram to realize the effect of interaction parameters on the coagulation values. The higher the mutual affinity of solvent to polymer (low Ï23), the faster is the liquid-liquid demixing rate to occur. For DCM solvent, fastest demixing rate was exhibited and lowest for the THF. Â© 2014 Trans Tech Publications, Switzerland.